Second-Year University Students’ Problem Encountered During Listening Process - M Arbain; H Novika (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The ultimate goal of language teaching is to enable learners to communicate in the target language they learn. For those who can meet this goal are regarded as high achievers or successful language learners. However, not every language learner can reach this goal. Listening is one the most important skill to have but unfortunately Listening is clearly considered as the weakest skill of EFL students who encounter different kinds of listening problems. It is the most underestimated skill in EFL context, though. This research is aimed at identifying the second-year university students’ problems encountered during listening process.